Comparison of properties of HAp and CaTiO3-HAp ceramic composite fabricated by different sintering conditions - Chiengsorn Rawisada; Lioroongcharoen Supimkarn; Charoenpanich Adisri; Chanadee Tawat (Science of Sintering)
A hydroxyapatite (HAp) ceramic and a 20 wt% CaTiO3-HAp ceramic composite for potential application as biomaterials were produced using single-step sintering (SS) and twostep sintering (TSS) in air. The sample pellets were SS sintered at 1250°C with a holding time of 1 h. For TSS, the pellets were heated at 10°C/min to 1250°C (T1) and held at this temperature for 20 min (t1). The temperature was then rapidly lowered at 20°C/min to 1150°C (T2), and held at this temperature for 10 min (t2). The 20 wt% CaTiO3-HAp ceramic composite obtained from TSS had a fine grain of 0.56 ± 0.04 μm due to the restraint of grain growth caused by the fast cooling from T1 to T2 and the hard CaTiO3 particles dispersed in the HAp matrix. The microstructure refinement of the 20 wt% CaTiO3-HAp ceramic composite fabricated by TSS produced suitable sintered density due to increased locking at triple junctions. This ceramic composite exhibited fracture toughness of 2.10 MPa.m1/2 with brittleness of 1.97 mm-1/2, indicating that crack propagation was suppressed. MG-63 osteoblast cells were able to adhere to the surface of both HAp and the 20 wt% CaTiO3-HAp ceramic composite produced by TSS and were no different between 3 and 7 days of culture. The alkaline phosphatase activity of MG-63 cells was higher on both ceramics cultured in osteogenic differentiation medium than in complete growth medium, which indicated more efficient osteoinductivity.